Do corporate tax cuts boost economic growth? - Sebastian Gechert; Philipp Heimberger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2021)
The empirical literature on the impact of corporate taxes on economic growth reaches ambiguous conclusions: corporate tax cuts increase, reduce, or do not significantly affect growth. We apply meta-regression methods to a novel dataset with 441 estimates from 42 primary studies. There is evidence for publication selectivity in favour of reporting growth-enhancing effects of corporate tax cuts. Correcting for this bias, we cannot reject the hypothesis of a zero effect of corporate taxes on growth. Several factors influence reported estimates, including researcher choices concerning the measurement of growth and corporate taxes, and controlling for other budgetary components.
Keywords: E60; H25; O40; 330; Corporate income taxes; economic growth; meta-analysis; Unternehmensbesteuerung; Steuersenkung; Wirtschaftswachstum; Welt